Exploring Education Character Thought of Ki Hajar Dewantara and Thomas Lickona - Asnawan Asnawan (International Journal on Advanced Science, Education, and Religion, 2020)
This article aimed to describe the idea of Ki Hajar Deantara and Thomas Lichona about the moral problems of today's society. Where the children’ experience moral degradation which seems increasingly out of control. This article used library research. Documentation and observation was used in collecting data. The research reveals that Ki Hajar Dewantara’s concept of education is to realize the achievement of educational goals through the Education Tripusat. According to Thomas Lickona, there are three kinds of moral knowledge that can be used when dealing with moral challenges, including moral awareness, knowing moral values, and determining perspective. Ki Hajar Dewantara argues that in order to carry out character education, understanding must be embedded, feeling something that is learned and then implementing it in real behavior. While, Thomas Lickona stated that the emotional side of character is the same as the intellectual side, open to the development of schools and families. Three moral aspects to teach about character include conscience, empathy, and humility. Keywords: Education Character, Degradation Moral in Society